2023
DOI: 10.1038/s41598-023-33444-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of silent phenotypes of calf antibiotic dysbiosis

Abstract: Reducing antibiotic usage among livestock animals to prevent antimicrobial resistance has become an urgent issue worldwide. This study evaluated the effects of administering chlortetracycline (CTC), a versatile antibacterial agent, on the performance, blood components, fecal microbiota, and organic acid concentrations of calves. Japanese Black calves were fed with milk replacers containing CTC at 10 g/kg (CON group) or 0 g/kg (EXP group). Growth performance was not affected by CTC administration. However, CTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Pairwise-based DirectLiNGAM, which uses a simple linear approximation to reduce the computational cost of the likelihood ratio, was later developed [3] . DirectLiNGAM has been applied to various data, such as medical and health data [ 7 , 8 ], metagenome and metabolome data [ 9 , 10 ], and financial data [11] . The background information is detailed in the ‘Additional Information’ section.…”
Section: Brief Informationmentioning
confidence: 99%
“…Pairwise-based DirectLiNGAM, which uses a simple linear approximation to reduce the computational cost of the likelihood ratio, was later developed [3] . DirectLiNGAM has been applied to various data, such as medical and health data [ 7 , 8 ], metagenome and metabolome data [ 9 , 10 ], and financial data [11] . The background information is detailed in the ‘Additional Information’ section.…”
Section: Brief Informationmentioning
confidence: 99%
“…Sheep provides wool along with good quality meat and milk due to which its role in the backyard and commercial farming cannot be neglected. Many approaches are being adapted for the proper growth and health of sheep among which use of natural products as therapeutic and growth promoting substances is gaining popularity from the past few decades (29)(30)(31). Research has found that GAS has strong functions such as antioxidation, detoxification, sterilization, disease prevention, and aiding digestion.…”
Section: The Effect Of Gas On the Growth Performance And Intestinal T...mentioning
confidence: 99%